Enhancement of ion beam charge states by electron vortices in a plasma optical device - Goncharov, A.; Maslov, V.; Brown, I. (Вопросы атомной науки и техники, 2005)
We consider the possibility of enhancing the ionization charge states of beam ions by electron vortices excited in cylindrically symmetric plasma optical systems of finite length with crossed radial electric and longitudinal magnetic fields.